Epidemiological study of genitourinary syndrome of menopause in Japan (GENJA study). Issue 4 (22nd April 2023) - Tomoe, Hikaru; Ozaki, Yumi; Yamamoto, Mayuko; Kuwajima, Mami; Ninomiya, Noriko; Sekiguchi, Yuki; Sato, Yoshikazu; Takahashi, Satoru; Nagao, Koichi
Abstract : The authors of this study conducted the first online survey using a Japanese-translated Vulvovaginal Symptoms Questionnaire and reported that the prevalence of genitourinary syndrome of menopause with genital or sexual symptoms in Japanese women aged 40 years and older was 11.6%, and 31.7% in sexually active women. Abstract: Objective: This study aimed to investigate the prevalence of genitourinary syndrome of menopause (GSM) in Japan using the Japanese translation of the Vulvovaginal Symptoms Questionnaire (VSQ) with online survey. In addition, we examined the relationship between sexual activity and GSM symptoms. Methods: An online survey on GSM was conducted with 4, 134 women aged 40 to 79 years, who were registered in an online survey company. Several questionnaires with Japanese translations of linguistic validity were used in this study. GSM was defined as a condition in women older than 40 years with vulvovaginal symptoms on the VSQ. Results: The percentage of postmenopausal women 40 years and older was 69.6%. The percentage of women with sexual activity was 22%. The prevalence of GSM with vulvovaginal symptoms was 11.6%, and 31.7% in sexually active women. The prevalence of GSM was associated with age and was significantly lower in the 70s age group than in other age groups. Vulvar hurting and dryness were both age-related only in the sexual activity group, with a statistically significantly higher prevalence in the 70s group than in the 40s group. The prevalence of vulvar dryness during sexual activity was significantly lower in the 40s age group. Conclusions: An online epidemiological survey of GSM was conducted for the first time in Japan using the linguistically validated Japanese translation of the VSQ. The prevalence of GSM with genital or sexual symptoms was 11.6% in Japanese women 40 years and older, and 31.7% in sexually active women.